A family with a milder form of adult dominant polycystic kidney disease not linked to the PKD1 (16p) or PKD2 (4q) genes. Issue 7 (July 1997) - Ariza, M; Alvarez, V; Marín, R; Aguado, S; López-Larrea, C; Alvarez, J; Menéndez, M J; Coto, E
Abstract : Autosomal dominant polycystic kidney disease (ADPKD) is a genetically heterogeneous disease. Most families show positive linkage to polymorphic markers around the PKD1 (16p13.3) or PKD2 (4q21-23) loci. The PKD1 and PKD2 genes have been cloned and mutations defined in a number of patients. Several clinical studies have described a milder phenotype for PKD2 patients. More recently, evidence for a third genetic locus has been found in one Portuguese, one French-Canadian, and one Italian family. We identified a Spanish family with negative linkage to the PKD1 and the PKD2 loci. This family showed a very mild clinical phenotype compared to the other forms of ADPKD, including the non-PKD1/non-PKD2 families previously described.